PHARMACOCORRECTION OF NSAID–GASTROPATHY IN RHEUMATOID ARTHRITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
RA belongs to the class of autoimmune diseases - when the body, instead of destroying natural enemies (disease-causing microbes, tumor cells, etc.), suddenly takes up arms against its own healthy tissues and begins to destroy them. With rheumatoid arthritis, the connective tissues of the joints are affected. Periarticular tissues such as ligaments and muscles can also become inflamed. RA is a frequent and one of the most severe immuno-inflammatory diseases in humans, which determines the great medical and socio-economic significance of this pathology.